Iloprost treatment on top of infrapopliteal angioplasty accelerates wound healing in critical leg ischemia. (February 2020) - K Ay, Nuray; Inan, Bekir
Objectives: This study aimed to examine the efficacy of the concomitant use of infrapopliteal drug-eluting balloon angioplasty and a medical treatment (iloprost) in the treatment of critical leg ischemia. Methods: Eighty-seven patients that underwent infrapopliteal drug-eluting balloon angioplasty for critical leg ischemia were included in this retrospective study. For analyses, patients were allocated into one of the two groups: 55 patients that underwent drug-eluting balloon angioplasty alone (drug-eluting balloon Group), and 32 patients that received intravenous iloprost for one week after drug-eluting balloon (DEB-I Group). Demographic, perioperative and follow-up clinical data were extracted retrospectively and analyzed. Results: Duration of hospitalization was significantly longer in the DEB-I group (9.7 vs. 3.1 days, p  < 0.001); however, the two groups were similar in terms of other clinical outcomes including early postoperative mortality, and primary patency, wound healing, reintervention, mortality, and amputation rates at one year ( p  > 0.05 for all). Primary patency was similar across groups. Wound healing occurred earlier in the DEB-I group when compared to drug-eluting balloon group, in the subgroup of patients with ischemic wound at baseline. Mean time to wound healing was 3.0 ± 0.6 and 4.4 ± 0.6 months in DEB-I and drug-eluting balloon groups, respectively ( p  = 0.037). Conclusions: Iloprost add-on treatment in patients undergoing drug-eluting balloon angioplasty for critical limb ischemia seems to have additional benefits, at least in terms of accelerated wound healing. Further large prospective studies are warranted.